L’impact des institutions internationales à Bruxelles : une approche multicritères - Eric Corijn; Cathy Macharis; Theo Jans; Michel Huysseune (Brussels Studies, 2008)
This paper develops an integrated assessment framework for costs and benefits related to the presence of international institutions in Brussels, Belgium. The assessment of the impact of international institutions in Brussels has until now been carried out in terms of macroeconometric cost-benefit analysis, mostly in monetary terms. We propose an alternative multi-criteria analysis with a spatial scope. The activities generating the impacts will be described through a multi-tiered analysis centred on the operations of the institutions (resident officers, meetings). The scope is then expanded to encompass directly dependent sectors (e.g. media and diplomatic representations), strongly influenced organisations (e.g. NGOs and transnational corporations), and all entities involved in the reproduction of institutions as such and the individuals who people them (e.g. housing, education and leisure). The role of international institutions as urban attractors which influence the evolution of tourism, education and cultural flows is also taken into account. It is an alterative to the mainstream, which in our view is unable to measure the impacts on the urban system and does not sufficiently inform urban planning such as the International Development Plan. The chosen methodology is a Multi-criteria Analysis Approach, more suited to integrating non-monetisable impacts and the views of stakeholders. Possible distributive effects will be tracked across existing patterns of spatial diversity. The proposed model embeds identification, measurement and assessment in a fine-grained understanding of Belgian urban systems, thus allowing the disaggregation and localisation of impacts. Through the iterative generation of scenarios, our methodology will support decision-makers in evaluating alternative federal policies for their ability to reduce negative impacts whilst enhancing the positive ones.